Can large-scale oblique undulations on a solid wall reduce the turbulent drag? - Ghebali,S; Chernyshenko,SI; Leschziner,MA (Physics of Fluids, 2017)
Direct numerical simulations of fully-developed turbulent channel flows withwavy walls are undertaken. The wavy walls, skewed with respect to the mean flowdirection, are introduced as a means of emulating a Spatial Stokes Layer (SSL)induced by in-plane wall motion. The transverse shear strain above the wavywall is shown to be similar to that of a SSL, thereby affecting the turbulentflow, and leading to a reduction in the turbulent skin-friction drag. Thepressure- and friction-drag levels are carefully quantified for various flowconfigurations, exhibiting a combined maximum overall-drag reduction of about0.5%. The friction-drag reduction is shown to behave approximatelyquadratically for small wave slopes and then linearly for higher slopes, whilstthe pressure-drag penalty increases quadratically. Unlike in the SSL case,there is a region of increased turbulence production over a portion of thewall, above the leeward side of the wave, thus giving rise to a local increasein dissipation. The transverse shear-strain layer is shown to be approximatelyReynolds-number independent when the wave geometry is scaled in wall units.